Sensorimotor activity partially ameliorates pain and reduces nociceptive fiber density in the chronically injured spinal cord - Sliwinski, Christopher; Nees, Timo A.; Puttagunta, Radhika; Weidner, Norbert; Blesch, Armin (Journal of neurotrauma, 2018)
A large proportion of patients suffering from spinal cord injury (SCI) develop chronic central neuropathic pain. Previously, we and others have shown that sensorimotor training early after SCI can prevent the development of mechanical allodynia. To determine whether training initiated in the subchronic/chronic phase remains effective, correlates of below-level neuropathic pain were analyzed in the hindpaws 5-10 weeks after a moderate T11 contusion SCI (50 kDyn) in adult female C57BL/6 mice. In a comparison of SCI and sham mice 5 weeks post-injury, about 80% of injured animals developed mechanical hypersensitivity to light mechanical stimuli, whereas testing of noxious stimuli revealed hypo-responsiveness. Thermal sensitivity testing showed a decreased response latency after injury. Without intervention, mechanical and thermal hyper-responsiveness were evident until the end of the experiment (10 weeks). In contrast, treadmill training (2 × 15 min/day; 5 × /week) initiated 6 weeks post-injury resulted in partial amelioration of pain behavior and this effect remained stable. Analysis of calcitonin gene-related peptide (CGRP)-labeled fibers in lamina III-IV of the lumbar dorsal horn revealed an increase in labeling density after SCI. This was not due to changes in the number or size distribution of CGRP-labeled lumbar dorsal root ganglion neurons. Treadmill training reduced the CGRP-labeling density in the spinal cord of injured mice, whereas the density of non-peptidergic isolectin-B4 (IB4)+ fibers showed no changes in lamina IIi and a slight reduction of sparse IB4 labeling in laminae III-IV. Thus, sensorimotor activity initiated in the subchronic/chronic phase of SCI remains effective in ameliorating pain behavior and influencing structural changes of the nociceptive system.